G71 With a little help from your friends – a collaborative simulation programme improves paediatric trainees' confidence in managing complex mental health presentations. (12th March 2018) - Shiri-Feshki, M; Mullen, N; Owen, B
Abstract : Objectives: Paediatric trainees encounter complex acute mental health presentations infrequently. We developed and assessed the impact of a collaborative Paediatric Mental Health simulation training programme for senior paediatric trainees (ST6–8). Methodology: The one day course was designed by a multi-professional and multidisciplinary team comprising: Children and Adolescent Mental Health Consultants and senior trainees Senior Acute psychiatry liaison nurses Paediatric Emergency Medicine Consultant Paediatric Simulation Lead Educationalists from Northumbria University Based on curriculum needs and the experience of the faculty we designed three challenging scenarios: A young person with anorexia nervosa and diabetes refusing treatment An agitated young person with challenging behaviour A young person refusing investigation and treatment following a substantial paracetamol overdose We used medical and nursing students as simulated patients following careful pre-brief. Using anonymous self-rating questionnaires we assessed the participants' confidence levels before, immediately after and 4 month after the course. We linked the pre and post-course questionnaires using the last three digits of the participants' post-codes. Results: We received 18 pre and immediate post course questionnaires. Of 18 questionnaires 15 were able to be matched immediately after the course. We also received 5 matched questionnaires after 4 months.The differences were calculated and the percentage of the means plotted. Immediate effects: The results showed an improvement in confidence in almost all domains. There was particular improvement in the domains labelled 'clinical patient care' and 'collaborative practice'. Medium effects (after 4 months): The results after 4 months showed sustained improvement in learners' confidence in the majority of domains. Conclusion: Our programme has resulted in an immediate and sustained improvement in paediatric trainees' confidence in managing complex acute mental health presentations. We attribute our success in meeting this crucial yet previously unmet need to collaboration between senior colleagues from paediatrics, psychiatry and education.